WHAT ARE THE EFFECTS OF USING COMPUTERS ON TEACHING DISABLED SCHOOL STUDENTS AT KARAK SCHOOLS IN JORDAN? - ABUNAWAS, MOUSA (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, it becomes very important to use technology in different educational fields as they have the potential to enhance the learning process and makes it more organized with les time and effort. ’’Technologies are described as essential tools in the educational system to improve teaching in different areas’’ ( Sandholtz, 1997, p. 5). Technology meets the need of students with different abilities and facilities. Students with special needs need to have special educational support to help them learn smoothly. In fact, many schools, institutions and universities have started to integrate technology such as computers to support disabled students. In fact, Manuguerra (2011) claims that ’’such technologies have the potential to fundamentally change the ways that learning and teaching are carried out,” which help students a lot (p. 2).